2010
DOI: 10.2147/jaa.s14419
|View full text |Cite
|
Sign up to set email alerts
|

Are adrenaline autoinjectors fit for purpose? A pilot study of the mechanical and injection performance characteristics of a cartridge- versus a syringe-based autoinjector

Abstract: Background:Adrenaline autoinjectors (AAIs) are prescribed to facilitate the intramuscular administration of adrenaline in patients diagnosed with life-threatening anaphylaxis. This pilot study investigated the injection and functional properties of two AAIs (deploying different delivery systems) under standard conditions, after dynamic and mechanical stresses, and in the presence of denim.Methods:The differences between a cartridge-based AAI (EpiPen® Junior) and a syringe-based AAI (Anapen® Junior) were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
1
25
1
1
Order By: Relevance
“…The four autoinjectors used in this study also showed same quantity of drug delivery. The injectable needle length was within the range and recommended for the autoinjector devices 12,13 . The autoinjectors meant for intramuscular injection in human being was used in the study with a modification of two volume deliveries -full volume injection and partial volume injection.…”
Section: Experiments In Rabbitsmentioning
confidence: 78%
“…The four autoinjectors used in this study also showed same quantity of drug delivery. The injectable needle length was within the range and recommended for the autoinjector devices 12,13 . The autoinjectors meant for intramuscular injection in human being was used in the study with a modification of two volume deliveries -full volume injection and partial volume injection.…”
Section: Experiments In Rabbitsmentioning
confidence: 78%
“…However, concerns about the mechanical performance of EAIs are reported from time to time [34,40,41]. [17] Manufacturers should work with the FDA to produce simple, well-designed devices, taking into consideration the human factors aspect and the physical environment that houses the device Zhang et al (2003) [18] Heuristic evaluation is a useful, efficient, low-cost method for evaluating patient-safety features of medical devices through the identification of usability problems and their severity Gurses et al (2012) [19] Human factors and ergonomics must play a more prominent role in accelerating improvements in patient safety Warburton (2005) [20] Changes aimed at error reduction must be implemented to be cost effective and with an understanding of HFE and safety science Lin et al (2001) [21] A new interface, designed using HFE, eliminated drug-concentration errors, while the simulated commercially available interface did not Price et al (1999) [22] HFE can improve device preference: most patient and nurses preferred Easi-Breathe over the conventional metered-dose inhaler for ease of use/training…”
Section: E S Edwards Et Almentioning
confidence: 99%
“…Es una de las 97 presentaciones de la relación de medicamentos fabricados por los Servicios Farmacéuticos del Ministerio de Defensa Español 28 , con número OTAN de Codificación -N.O.C.-6505 33 0051675, y Código Nacional -C.N.-número 698712. Está indicado en el tratamiento de la exposición a agentes nerviosos (neurotóxicos).…”
Section: Autoinyectable De Atropina-oxima Def (Ai-aod)unclassified